Mastering your Fellowship - K. B. von Pressentin; M. Naidoo; T. Ras; M. Torlutter (South African Family Practice)
The series, “Mastering your Fellowship”, provides examples of the question format encountered in the written and clinical examinations, Final Part A of the FCFP(SA) examination. The series is aimed at helping family medicine registrars prepare for this examination. Model answers are available online.